2020
DOI: 10.1002/admt.202000284
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Surfactant Exfoliation of Graphene and Conductivity‐Optimized Graphite Enabling Wireless Connectivity

Abstract: Graphene and other graphitic materials are suggested as a route to cheap, high‐performance, environmentally‐sustainable electronic devices owing to their almost unique combination of properties. Liquid‐phase exfoliation is a family of shear‐based techniques that produce dispersions of nanosheets from bulk layered material crystallites. High‐quality nanosheets of graphene can be produced in solvents or surfactant dispersions; however the lateral size of these sheets limits the network transport properties obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Graphene was produced by high shear exfoliation in a Mini DeBEE homogenizer from BEE International at 35kpsi for 10 passes using 60g/L graphite to 4g/L Triton X-100 (CAS# 9002-93-1). Full details of the dispersion procedure are published in previous work [22]. The material was centrifuged at 5000g for 6 minutes to remove large aggregates and then centrifuged at 5000g for 1 hour to remove the few layer graphene as well as leave unbound surfactant in the supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…Graphene was produced by high shear exfoliation in a Mini DeBEE homogenizer from BEE International at 35kpsi for 10 passes using 60g/L graphite to 4g/L Triton X-100 (CAS# 9002-93-1). Full details of the dispersion procedure are published in previous work [22]. The material was centrifuged at 5000g for 6 minutes to remove large aggregates and then centrifuged at 5000g for 1 hour to remove the few layer graphene as well as leave unbound surfactant in the supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…Graphene dispersions in cyclohexanone were processed as described in Large et al 24 . Sizeselected graphene dispersions were required.…”
Section: Methodsmentioning
confidence: 99%
“…It is a general perception that the electrical conductivity of films constituted with exfoliated graphene nanosheets is low owing to the smaller lateral size and presence of surfactants. Large et al recently reported a printed graphene film with excellent conductivity up to 50,000 S/m, which is one order of magnitude higher than that reported by Karagiannidis et al [49]. The printable graphene ink was prepared via a high-pressure homogenization process (microfluidization), enabling a high throughput of 0.5 g h −1 graphene nanosheet production, equivalent to almost 5 kg of graphene nanosheets per year.…”
Section: Microfluidizationmentioning
confidence: 97%